Effect of alternate fill pattern on mechanical properties of FDM printed PC-PBT alloy. (2022) - Singhal, Prachi; Sujithra, R.; Saritha, D.
Abstract: This study investigates the effect of alternate fill pattern, infill density, and annealing on tensile, flexural, short-beam strength, and fracture toughness of PC-PBT alloy printed by the FDM process. The alternate fill pattern is printed as similar to multilayer sandwich panels, linear fill pattern as skin and hexagonal (honeycomb) pattern as sandwich in between the linear pattern. Two sets of samples are printed, one with the alternate fill pattern of linear and hexagonal with 100% fill density and another with alternate fill density of 100% in linear and 70% in the hexagonal pattern are tested, without and with annealing. The tensile experimental result indicates that alternate fill pattern leads to brittle failure with the drastic reduction in the tensile strain at break compared with the standard value of PC-PBT. But the flexural modulus is significantly higher than the standard value. The flexural strength, short-beam strength, and plain-strain fracture toughness are high for alternate fill patterns with alternate infill densities of 100% and 70%. Annealing below glass transition temperature has a more significant effect on fracture toughness for the alternate fill pattern with alternate fill density (100% and 70%), and minor impact on tensile, flexural and short-beam strength. The printed alternate pattern has high fracture toughness as similar to composite.